Anti-citrullinated protein antibodies and high levels of rheumatoid factor are associated with systemic bone loss in patients with early untreated rheumatoid arthritis. Issue 1 (December 2016) - Bugatti, Serena; Bogliolo, Laura; Vitolo, Barbara; Manzo, Antonio; Montecucco, Carlomaurizio; Caporali, Roberto
Abstract Background Autoantibodies such as anti-citrullinated protein antibodies (ACPA) are major risk factors for articular bone destruction from the earliest phases of rheumatoid arthritis (RA). The aim of the current study was to determine whether RA-associated autoantibodies also impact on systemic bone loss in patients with early disease. Methods Systemic bone mineral density (BMD) was measured in the lumbar spine and the hip in 155 consecutive treatment-naïve patients with early RA (median symptom duration 13 weeks). Demographic and disease-specific parameters, including clinical disease activity, ultrasonographic (US) examination of the hands and wrists, radiographic scoring of joint damage, ACPA and rheumatoid factor (RF) levels were recorded from all patients. Reduced BMD was defined as Z score ≤ -1 SD and analysed in relation to disease-related characteristics and autoantibody subgroups. Results Reduced BMD was found in 25.5 % of the patients in the spine and 19.4 % in the hip. Symptom duration, clinical and US disease activity, functional disability and radiographic damage did not significantly impact on spine and hip BMD loss in regression analyses adjusted for possible confounders (age, gender, menopausal status, current smoking, body mass index). In contrast, ACPA positivity (at any level) negatively affected the spine Z-score (adjusted OR (95 % CI) 2.76 (1.19 to 6.42)); the hip Z score was affected by high titres only (adjusted OR (95 % CI) 2.96 (1.15 to 7.66)). The association of ACPA with reduced BMD in the spine was confirmed even at low levels of RF (adjusted OR (95 % CI) 2.65 (1.01 to 7.24)), but was further increased by concomitant high RF (adjusted OR (95 % CI) 3.38 (1.11 to 10.34)). In contrast, Z scores in the hip were significantly reduced only in association with high ACPA and RF (adjusted OR (95 % CI) 4.96 (1.48 to 16.64)). Conclusions Systemic BMD in patients with early RA is reduced in relation with ACPA positivity and high RF levels. This finding supports the notion that RA-associated autoimmunity may have a direct causative role in bone remodeling.